Ryan's dilemma - Vohra, Neharika, 1966-; Agarwalla, Smirti; Basoya, Snehil (London : Indian Institute of Management, Ahmedabad, 2018)
The case centers on Ryan Bansal, a recent business graduate, who attempts to affect change in his family business using the theoretical knowledge he acquired at University. The case illustrates the complexities of family business and the difficulties of implementing organizational change.
Originally Published In Vohra, N., Agarwalla, S., & Basoya, S. (2018). Ryan's Dilemma. CIIE0012. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bansal, Ryan; Family-owned business enterprises -- Management -- Case studies; Organizational change -- Case studies